Cetirizine: A new and effective corrosion inhibitor for mild steel in 1 M HCl solution - Singh P.; Singh A.; Quraishi M.A.; Ebenso E.E. (My University, 2025)
Cetirizine was investigated as corrosion inhibitor for mild steel (MS) in 1 M HCl solution by weight loss, electrochemical measurements and quantum chemical calculations. Cetirizine showed 95% inhibition efficiency even at very low concentration of 100 ppm. Polarization study indicates that Cetirizine behaves like a mixed type inhibitor. The adsorption of the inhibitor follows Langmuir adsorption isotherm. The quantum chemical calculations were applied to elucidate adsorption pattern of inhibitor molecules on steel surface.© 2012 by ESG.